2022
DOI: 10.3389/fbioe.2022.895998
|View full text |Cite
|
Sign up to set email alerts
|

CD73-Positive Small Extracellular Vesicles Derived From Umbilical Cord Mesenchymal Stem Cells Promote the Proliferation and Migration of Pediatric Urethral Smooth Muscle Cells Through Adenosine Pathway

Abstract: Smooth muscle cells (SMCs) are the main functional component of urethral tissue, but are difficult to proliferate in vitro. Mesenchymal stem cells (MSCs) and mesenchymal stem cell-derived small extracellular vesicles (MSC-sEV) have been shown to promote tissue repair by regulating the proliferation and migration of different types of cells. In this study, we investigated the effect of umbilical cord mesenchymal stem cell-derived sEV (UCMSC-sEV) on the proliferation and migration of pediatric urethral smooth mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…Yao et al found that MSC-Exos inhibited the EMT process of endometrial epithelial cells via the TGF-β1/Smad signaling pathway, thus promoting endometrial repair [ 13 ]. Xiao et al reported that miR-23a-3p and miR-182-5p transferred by MSC-Exos inhibited the NF-κB and Hedgehog pathways by silencing Ikbkb and destabilizing IKKβ, thus reversing the EMT process in LPS-induced pulmonary injury [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Yao et al found that MSC-Exos inhibited the EMT process of endometrial epithelial cells via the TGF-β1/Smad signaling pathway, thus promoting endometrial repair [ 13 ]. Xiao et al reported that miR-23a-3p and miR-182-5p transferred by MSC-Exos inhibited the NF-κB and Hedgehog pathways by silencing Ikbkb and destabilizing IKKβ, thus reversing the EMT process in LPS-induced pulmonary injury [ 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…Mesenchymal stem cell–derived small extracellular vesicles (MSC-sEVs) perform well in tissue damage repair, immune regulation, and promoting angiogenesis [ 10 , 11 ]. We have found that umbilical cord mesenchymal stem cell exosomes (UCMSC-exo) can significantly promote the proliferation and migration of pediatric urethral smooth muscle cells (PUSMCs) in vitro by delivering CD73 molecules to PUSMCs and catalyzing the production of adenosine (ADO) and that the PI3K/AKT signaling pathway in PUSMCs is activated after ADO or UCMSC-exo intervention [ 12 ]. Based on this, we hypothesized that the effect of PU-MSLCs on urethral repair may be accomplished through the proangiogenic effect of PU-MSLC-derived small extracellular vesicles (PUMSLC-sEVs) and that CD73 molecules and ADO (a CD73 metabolite) promotes angiogenesis.…”
Section: Introductionmentioning
confidence: 99%